If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(b + 6) + -3 = 46 Reorder the terms: 7(6 + b) + -3 = 46 (6 * 7 + b * 7) + -3 = 46 (42 + 7b) + -3 = 46 Reorder the terms: 42 + -3 + 7b = 46 Combine like terms: 42 + -3 = 39 39 + 7b = 46 Solving 39 + 7b = 46 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-39' to each side of the equation. 39 + -39 + 7b = 46 + -39 Combine like terms: 39 + -39 = 0 0 + 7b = 46 + -39 7b = 46 + -39 Combine like terms: 46 + -39 = 7 7b = 7 Divide each side by '7'. b = 1 Simplifying b = 1
| 35=3y | | 4+12x-8x+3=31 | | -32/-3 | | 27y+-6=-3+3y | | 3x+2(-1)-22x+(3+x)=5 | | 8x+35=-3 | | -13=a+3 | | x^2+8x^2=-15x | | 9c=27 | | n/-4=11 | | 9c=20 | | 30(20)-10(1x)=15(1x) | | (-2-6i)-(4-6i)=0 | | (n)(n)= | | a^9/a^5 | | 2(y-9)=3y-4 | | -n^2-7n-10= | | p-11=-11 | | 38+7k=8 | | 4x^2+44x+121=0 | | 3(5-10)=x-4 | | 5=30b | | 12=-3(2x+2) | | (A+b)x=a+b | | 3(x-9)+4=8(4-8x) | | q^2-6q+35= | | -6x+17=3(1+x)-9x | | 6=4y-3y+2 | | 2k+7k=45 | | 3u^2+16u+5=0 | | 3+v=1 | | 79(y-50)=y-25 |